Calculation of quarzite crystallinity index by infrared absorption spectrum; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Razva O.; Anufrienkova A.; Korovkin M. V. Mikhail Vladimirovich; Ananieva L. G. Ludmila Gennadievna; Abramova R. N. Raisa Nikolaevna (Mineralogy, Geochemistry and Petrography, 2014)
Title screen